Producción de la industria textil y su incidencia en las exportaciones, Ecuador, periodo 2012 – 2014 - Hidalgo Quijije, Yomaira Isabel (2016)
The textile industry is the industrial sector that generates a lot of direct and indirect jobs in the economy and is linked to foreign trade. This research aims to evaluate textile production of Ecuador and its impact on the international market during the period 2012 to 2014. In recent years there has been a reduction in exports influenced by various factors such as the lack of bilateral agreements with other countries, which is why to clearly define the impact of textile production in the international market, data were collected in companies and public and private institutions whose information was processed and analyzed by deductive, inductive, analytical and analytical methods. Among the main findings is to be in 2014 the 61.16% of exports of textile products as fabrics and materials of Ecuador, are basically to countries belonging to the Andean Community of Nations, while the domestic textile production in the period 2012 2014 affects the economy by an average of 1.80%. Ecuador considered with other countries in the region not represented as a producer of large-scale textile sector. The lack of technology, stagnation in innovation and creation of new brands are some of the factors that influence negatively on production volume and export volume for that reason it is difficult to meet the expectations and domestic demand and international.